The physical review of sound waves propagation into the human cochlea - B. Mohamed, Mohamed (Libyan Journal of Science &Technology, 2024)
In the last three decades, medicine and technology have evolved a lot and have permitted to solve and provide many treatments considered impossible before that period. One of these hopeless cases that of interest to many people are the cochlear implants that are associated with deafness. This paper discusses the human ear anatomy and the physics of the interaction of sound waves in the cochlea.